2019
DOI: 10.13057/biodiv/d200611
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Leaf architectural analysis of taxonomically confusing coffee species: Coffea liberica and Coffea liberica var. dewevrei

Abstract: Abstract. Baltazar AMP, Buot JrIE. 2019. Short Communication: Leaf architectural analysis of taxonomic confusing coffee species: Coffea liberica and Coffea liberica var. dewevrei. Biodiversitas 20: 1560-1567. Coffee is considered as one of the most important crops. The Philippines is known to produce four coffee varieties namely: Arabica (Coffea arabica), Robusta (Coffea canephora), Excelsa (Coffea liberica var. dewevrei) and Liberica (Coffea liberica). Further, the taxonomy of C. liberica and C. liberica var.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
2
10
0
1
Order By: Relevance
“…Even with limited dissimilar characters, the analysis showed that all species exhibit variability in the laminal and venation characters, and thus are distinct from one another. The study agreed with the findings of Roth-Nebelsick et al (2001) and many others (Buot 2020;Paguntalan and Buot 2019;Baltazar and Buot 2019a;Baltazar and Buot 2019b;Baltazar and Buot 2019c) that leaf architectural characters are genetically fixed and hence, can be used favorably in taxonomic studies, especially when dealing with controversial taxa as S. aqueum and S. samarangense.…”
Section: Statistical Analysis Of Leaf Architectural Characteristics Of S Aqueum S Samarangense and P Guajavasupporting
confidence: 90%
“…Even with limited dissimilar characters, the analysis showed that all species exhibit variability in the laminal and venation characters, and thus are distinct from one another. The study agreed with the findings of Roth-Nebelsick et al (2001) and many others (Buot 2020;Paguntalan and Buot 2019;Baltazar and Buot 2019a;Baltazar and Buot 2019b;Baltazar and Buot 2019c) that leaf architectural characters are genetically fixed and hence, can be used favorably in taxonomic studies, especially when dealing with controversial taxa as S. aqueum and S. samarangense.…”
Section: Statistical Analysis Of Leaf Architectural Characteristics Of S Aqueum S Samarangense and P Guajavasupporting
confidence: 90%
“…dewevrei 17,46 . Morphological and molecular data 37,42,[47][48][49] support the recognition of two varieties for C. liberica: var. liberica and var.…”
Section: Excelsa Coffeementioning
confidence: 76%
“…The apt epithet 'excelsa' has persisted and is still the most widely used common name for var. dewevrei 17,36,37,[47][48][49] . Excelsa is used in the remaining narrative for var.…”
Section: Excelsa Coffeementioning
confidence: 99%
“…Kopi Liberika merupakan nama lain dari kopi Excelsa yang sekarang lebih popular [7]. Namun peneliti lain menyatakan bahwa Liberika dan Excelsa keduanya digolongkan sebagai kopi Liberoid yang memiliki karakteristik yang berbeda [8], [9].…”
Section: Pendahuluanunclassified